DEVELOPING CTL-BASED AUTHENTIC READING MATERIALS FOR STUDENTS OF MINING ENGINEERING STUDY PROGRAM AT POLITEKNIK NEGERI KETAPANG - Syarifah Mastura; Y Gatot Sutapa Y; Ikhsanudin Ikhsanudin (Journal of English Educational Study (JEES), 2022)
This study aimed to design an authentic reading material for students of Politeknik Negeri Ketapang Program Studi Teknik Pertambangan. The goal was to design teaching material thus the students understand the text being read if the content is close to the students’ environment. The content of the product was based on the instructional objective mentioned on the syllabus. Each unit of the learning material design discusses different topics by implementing the components of Contextual Teaching and Learning (CTL). The components of Contextual Teaching and Learning were divided into three main activities, warm-up (pre-activity), whilst activity, and post activity). The participants of the research were the second semester students of Mining Engineering study program, consist of 43 students. The result of this study was described qualitatively. The results indicated that the materials were already effective and practical, it covered the students target language and the field of study, understandable and interesting. Lecturers and students can use this material easily, it can increase the students’ interest (practicalities). The material design provided new learning content, set with students’ interest, and provided the students with the clear target in learning (effectiveness).